Prediction and experimental validation of composite strength by applying modified micromechanics for composites containing multiple distinct heterogeneities - Jung, Hana; Choi, Hoi Kil; Yu, Jaesang (ELSEVIER SCI LTD, 2016)
The mechanical properties, such as strength and stiffness, of epoxy-based composites containing MWCNTs were experimentally and theoretically investigated. The classical analytic homogenization approach, called the Mori-Tanaka model, was firstly modified and reported to predict strength properties for composites containing multiple heterogeneities. In the modified Mori-Tanaka micromechanical strength modeling, the composites were considered as a two-phase simple model, as well as multiple heterogeneity case. The values obtained here were compared to experimentally measured data. The specimens reinforced with heterogeneities such as multi-walled carbon nanotubes (MWCNTs) were mainly fabricated and tested to measure the strength and stiffness of epoxy-based composites. When comparing the experimentally measured data of those composites with the predicted values obtained from the modified micromechanics models, it was confirmed that the developed approach successfully captures the effect of different types of heterogeneity on the resulting strength and stiffness of composites containing different geometrized nanofillers. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: THERMAL-CONDUCTIVITY; ELECTRICAL-PROPERTIES; THEORETICAL APPROACH; CARBON NANOTUBES; DISPERSION; MATRIX; NANOPLATELETS; TOUGHNESS